An economic analysis of the financial records of al-Qa'ida in Iraq - Bahney, Benjamin (RAND, 2010)
This monograph analyzes the finances of the militant group al-Qa'ida in Iraq (AQI) in Anbar province during 2005 and 2006, at the peak of the group's power and influence. The authors draw on captured documents that give details on the daily financial transactions of one specific sector within Anbar province and of the financial transactions of the AQI provincial administration. Some of their conclusions are: AQI was a hierarchical organization with decentralized decisionmaking; AQI in Anbar was profitable enough to send substantial revenues out of the province in 2006; AQI relied on extortion, theft, and black market sales to fund its operations in Anbar; AQI needed large, regular revenue sources to fund its operations, but its administrative leaders did not hold much cash on hand. The authors' interpretation of data on compensation practices and participants' risk of death indicates that AQI members were poorly compensated and suggests that they were not motivated primarily by money to join the group. The authors also find that mounting attacks required organizational expenditures well beyond the cost of materiel used in attacks. One major conclusion is that disrupting AQI's financial flows could disrupt the pace of their attacks.